Effect of Heat Treatment on Mechanical Properties and Ballistic Performance of Ti-4Al-2.3V-1.9Fe Alloy. (2015) - Sukumar, G.; Singh, B. Bhav; Bhattacharjee, Amit; Sivakumar, K.; Gogia, A.K.
Abstract: Effect of heat treatment on mechanical properties and ballistic performance of a new α+β titanium alloy Ti–4Al–2.3V-1.9Fe against 7.62 mm ball projectiles was studied. A 20 kg ingot of Ti-4Al-2.3V-1.9Fe was produced by vacuum arc remelting and thermo-mechanically processed to 15 mm thick plates. These plates were subjected to different heat treatments and their mechanical properties and ballistic performances were evaluated. Plates that were solution treated below the β-transus temperature followed by aging exhibited good combination of strength and ductility and better ballistic performance.